Employment in Spanish regions: Cost control or growth-enhancing policies? - Roberto Bande; Marika Karanassou; Hector Sala (Queen Mary University of London, School of Economics and Finance, 2017)
Spain provides an extreme case of unemployment rate oscillations (8.3% in 2007, 26.1% in 2013, 19.6% in 2016) in parallel with cute regional persistance in labour market outcomes - the sets of relatively high and low unemployment regions have not changed in decades. Since generic labour market reforms have been fruitless in this respect, we explore whether such groups of regions react differently to key drivers of employment and wage setting. We find that the low income (high unemployment) regions are more reactive to capital accumulation, and thus to a growth strategy based on estimulating investment. In turn, the high income (low employment) ones are more sensitive to the wage-productivity gap, and thus to the strategy that keeps unit labour costs (ULC) low. Such patterns call for more region-specific policies and discard standard labour market reforms as a unique toolto manage the unemployment rate problem. Further, to the extent that investment serves both at fostering capital accumulation and labour productivity (which, in turn, reduces the ULC), regionally-targeted soft credit lines and capital taxes could be helpful in breaking regional sluggishness.
Keywords: R11; E24; E22; J23; J31; 330; Employment; Wage setting; Labour income share; Capital stock